The Way of Production, Application, and Efficacies of DNA Vaccines in the Prevention of Diseases - Hakim, Hakimullah (Journal of Natural Sciences – Kabul University, 2020)
Outbreaks of diseases remain one of the most important challenges for the animal industry and public health. Throughout history, vaccination has played a fundamental role in the control and prevention of infectious diseases. However, the efficacy of vaccines needs to be continually reviewed, and their safety should be monitored. Recent advances in molecular biology have increased the possibility of creating new vaccines, such as DNA vaccines. Compared to conventional vaccines, DNA vaccines are safer, cheaper, and easier to maintain and transport. The present study aims to provide an overview of the current advancements in DNA vaccine technology, including their production mechanisms, applications, efficacy, and their advantages in disease prevention.